Facile preparation of tremella-like TiO2/Cd:ZnIn2S4 photoanode with enhanced photo-electro-chemical (PEC) performance for energy and environmental applications. (November 2022) - Li, Zengxing; Ng, Kim Hoong; Xu, Shen; Zhang, Yingzhen; Lei, Yonggang; Huang, Jianying; Lai, Yuekun
Abstract: The realization of solar-driven photoelectrochemical (PEC) process lies in the success development of materials with excellent photoelectric properties. Past reports identified TiO2, upon modified with both Cd and ZnIn2 S4 (ZIS), exhibits promising PEC performance; however, at the cost of tedious preparation. In view of this, our work proposes a facile one-step hydrothermal strategy to deposit both modifiers onto the pre-obtained TiO2 nanotubes (NTs), realizing rose-like TiO2 /ZnIn2 S4 (TiO2 /ZIS) or tremella-like TiO2 /Cd:ZnIn2 S4 (TiO2 /Cd:ZIS) with improved PEC performances. Interestingly, the thickness of ZIS petals, which deposited on top of TiO2 NTs, is positively-correlated to its Cd-composition, signifying the substitutional doping of Cd into the unit cell of ZIS. This renders robust ionic interactions between the constituents, prompting the enhanced optical properties of TiO2 in conjecture to its reduced impedance. As a result, the recombination rate of photo-electric-derived carriers was drastically suppressed, with an improved photocurrent density of 606.2 μA cm −2 recorded by TiO2 /Cd:ZIS photoanode under solar irradiation. Such performance is 80 times and 5.16 times higher than those of bare TiO2 NTs and TiO2 /ZIS counterparts. The photoconversion efficiencies in terms of incident photon-to-current conversion efficiency (IPCE) and applied bias photon current efficiency (ABPE) for TiO2 /Cd:ZIS were significantly improved too, recorded at 1.12% and 0.38%, respectively, under standard evaluation condition. As summary, our work proposes a facile one-step hydrothermal approach that simultaneously-deposit both Cd and ZIS onto TiO2 photoanode for an enhanced PEC performance. This opens up a wider horizon for PEC technology, further unlocking its potential in both energy and environmental applications. Graphical abstract: Image 1 Highlights: Tremella-like TiO2 /Cd:ZnIn2 S4 was prepared using one-step hydrothermal method. TiO2 photoanode was successfully sensitized over co-deposition of Cd and ZnIn2 S4 . TiO2 /Cd:ZnIn2 S4 secured 80-fold photocurrent enhancement against TiO2 NTs. Photo-charges were spatially-separated following Type-II heterojunction mechanism.